Effectiveness Of Electronic Holding Rights Registration (Ht-El) At The Tasikmalaya City Land Office - Putri Herfawan, Maurynesa; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The emergence of technological developments has forced the Government to implement a new system in all fields, one of which is Electronic Mortgage Rights (HT-el) in order to speed up the land registration process at the National Land Agency (BPN). However, the system experienced various procedural and technical problems, such as system maintenance and errors in the HT-el registration process that occurred in Kantah, Tasikmalaya City. This study aims to analyze the implementation of the cancellation of Electronic Mortgage registration due to the delay in completing the registration file and the effectiveness of the implementation of electronic Mortgage registration at the Tasikmalaya City Land Office. This research is a sociological juridical legal research and uses descriptive qualitative analysis techniques. The results of this study indicate that a) the implementation of the cancellation of the Electronic Mortgage Right will result in the cancellation of the revocation and the system will automatically delete the registration application, so that the PPAT must submit a new HT-el registration application, issue a new PNBP Deposit Order for payment of re-registration, and The PPAT will still be held liable in a civil manner if there is a loss for the parties. And b) the effectiveness of the implementation of HT-el registration at the Tasikmalaya City Land Office at this time after the COVID-19 pandemic, it is felt that the HT-el registration process is quite good but not optimal because there are still several obstacles so that the implementation of HT-el is not in accordance with existing procedures on Juknis HT-el. There needs to be a solution to overcome the obstacles that occur internally and externally.